2011
DOI: 10.1038/eye.2011.151
|View full text |Cite
|
Sign up to set email alerts
|

Visual and non-visual factors associated with patient satisfaction and quality of life in LASIK

Abstract: Purpose The aim of this study was to determine how laser in situ keratomileusis (LASIK) affects quality of life (QOL) and to identify factors that may affect satisfaction after LASIK. Methods A total of 104 patients with a mean age of 29±6, treated with LASIK for myopia and astigmatism, were enrolled in a prospective study. High (90%) and low (10%) contrast visual acuity (CVA) were measured under photopic and scotopic conditions before surgery and at 3 months later. A multidimensional QOL scale (Institute for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…8,46,47 In the PROWL studies, satisfaction with vision increased from baseline, but 1% (95% CI, 0%-4%) to 4% (95% CI, 2%-7%) of participants had some level of dissatisfaction with vision 3 to 6 months after surgery. The total number of dissatisfied participants in the PROWL studies was too small to assess associations with other factors.…”
Section: Discussionmentioning
confidence: 99%
“…8,46,47 In the PROWL studies, satisfaction with vision increased from baseline, but 1% (95% CI, 0%-4%) to 4% (95% CI, 2%-7%) of participants had some level of dissatisfaction with vision 3 to 6 months after surgery. The total number of dissatisfied participants in the PROWL studies was too small to assess associations with other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Improved satisfaction and function lead to a significant change in psychological characteristics of the patients, including a more positive attitude toward life following keratorefractive surgery, which was thought to be due to a decrease in the frequency of disturbing visual and ocular symptoms. 6 Tahzib et al 56 Similarly, patient satisfaction after PRK is excellent. Guerin et al 57 2-year follow-up of 120 patients who underwent myopic PRK found that 100% of patients would want to have the surgery again.…”
Section: ' Overall Patient Satisfactionmentioning
confidence: 95%
“…In general, while quality of life has been shown to improve significantly following refractive surgical procedures, 6 we plainly tell patients that we expect their postoperative uncorrected distance visual acuity (UCDVA) to be equal to preoperative best-corrected distance visual acuity (BCDVA). Many studies have shown that some percentage of patients will gain lines in best-corrected visual acuity following refractive surgery, but this is not true of a majority of patients.…”
Section: ' Preoperative Patient Counselingmentioning
confidence: 98%
“…Patient satisfaction following LASIK is related to post‐operative visual function; however, pre‐operative expectations and psychological characteristics are heavily related to the perceived success of the procedure . The potential patient must be thoroughly counselled to assess visual requirements and post‐operative expectations.…”
Section: Patient Selectionmentioning
confidence: 99%